2022
DOI: 10.12688/wellcomeopenres.17261.1
|View full text |Cite
|
Sign up to set email alerts
|

Defective iron homeostasis and hematological abnormalities in Niemann-Pick disease type C1

Abstract: Background: Niemann-Pick disease type C1 (NPC1) is a neurodegenerative lysosomal storage disorder characterized by the accumulation of multiple lipids in the late endosome/lysosomal system and reduced acidic store calcium. The lysosomal system regulates key aspects of iron homeostasis, which prompted us to investigate whether there are hematological abnormalities and iron metabolism defects in NPC1. Methods: Iron-related hematological parameters, systemic and tissue metal ion and relevant hormonal and proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Gene ontology (GO) analysis on biological processes showed an enrichment in proteins related to vesicle and vacuole fusion and organization, ion homeostasis and transport (namely, iron, manganese, and calcium), polyphosphate metabolism, Golgi organization, autophagy, and protein targeting to vacuole ( Figure 2 D and Supplementary Table S3 ). These results suggest that vesicle trafficking pathways and ion homeostasis are altered in yeast cells lacking Ncr1, being consistent with previously reported trafficking defects and calcium/iron dyshomeostasis [ 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 42 , 43 , 44 , 46 , 47 , 58 ] and alterations in the expression of lysosomal proteins related to autophagy in NPC [ 27 ]. A previous study with the yeast model also showed that Ncr1 interacts with vacuolar proteins, including the Pmc1 Ca 2+ ATPase and the Fth1 iron transporter.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Gene ontology (GO) analysis on biological processes showed an enrichment in proteins related to vesicle and vacuole fusion and organization, ion homeostasis and transport (namely, iron, manganese, and calcium), polyphosphate metabolism, Golgi organization, autophagy, and protein targeting to vacuole ( Figure 2 D and Supplementary Table S3 ). These results suggest that vesicle trafficking pathways and ion homeostasis are altered in yeast cells lacking Ncr1, being consistent with previously reported trafficking defects and calcium/iron dyshomeostasis [ 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 42 , 43 , 44 , 46 , 47 , 58 ] and alterations in the expression of lysosomal proteins related to autophagy in NPC [ 27 ]. A previous study with the yeast model also showed that Ncr1 interacts with vacuolar proteins, including the Pmc1 Ca 2+ ATPase and the Fth1 iron transporter.…”
Section: Resultssupporting
confidence: 92%
“…A tendency for iron levels to be higher in post-mortem human NPC1 cerebellar tissue and lower in plasma was also observed [ 42 ]. Recently, Chen et al detected lower levels of ferritin in the cerebrospinal fluid of NPC1 patients, consistent with alterations in iron homeostasis in the central nervous system [ 46 ]. Indeed, the authors showed that Npc1 −/− mice and NPC1 patients have significantly reduced serum iron and several hematological changes characteristic of iron deficiency anemia.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations